Does gamified elements influence on user's intention to adopt and intention to recommend internet banking?. Issue 1 (7th January 2019) - Rahi, Samar; Abd. Ghani, Mazuri
Abstract : Purpose: Understanding the main determinants of internet banking is important for banks and users. Although several prior research projects have focused on the factors that impact on adoption of technology, there is a limited empirical work which simultaneously captures technology-specific factors (PE, EE, WD, GAM) and customer-specific factors (GSC, INTRC) that help customers to adopt internet banking. Thus, the purpose of this paper is to verify how these factors influence individual behavior and motivate them to adopt new technology. The authors advance the body of knowledge on this subject by proposing moderating relationship of gamification between user's intention to adopt and intention to recommend internet banking in social network. Design/methodology/approach: To test the model the authors developed a quantitative study involving 398 internet users from five commercial banks. Data were collected in four weeks beginning of September 2017 from three large cities of Pakistan using convenience sampling approach. The theoretical model was tested using structural equation modeling (SEM). Findings: The results indicate that intention to adopt internet banking is positively affected by performance expectancy, effort expectancy, website design, website characteristics and general self-confidence. Findings of SEM showed that approximately 72 percent of the variance in customer's intention to adopt internet banking was accounted by predictors. Moderating effect of gamification suggested that the positive relationship between customer's intention to adopt and customer's intention to recommend internet banking will be stronger when gamification is higher. Importance performance matrix analysis (IPMA) suggested that among all other variables general self-confidence is the most important construct as it has the highest importance value in IPMA. Practical implications: This study provides insightful guideline to practitioners, web designers and marketing professional that they should focus on both technology perspective and customer-specific factors to boost the confidence of internet banking users, while for researchers this study provides a basis for further development of technology adoption models in e-commerce domain. Originality/value: This study contributes to the body of knowledge by adding game elements in technology perspective model and augments the e-commerce literature in the internet banking adoption context. To the date, this study is the first in its nature that investigates both technology-specific factors and customer-specific factors altogether to see the users influence toward technology adoption.